A prose of ambivalence: Liberation struggle discourse on necklacing - Moosage, Riedwaan (Kronos: Southern African Histories, 2017)
This article is concerned with the ambivalence that permeates liberation struggle discourse on the practice of necklacing. Through examining what was said about the killing of suspected collaborators and/or necklacing during the mid- to late 1980s by leaders of the African National Congress (ANC) and the United Democratic Front (UDF), I argue that those public positions produced a prose of ambivalence. I ask how this prose of ambivalence was produced and why that ambivalence is seemingly rendered intangible. I suggest that the ANC and UDF were caught in a double bind. They could not explicitly condemn the practice and risk losing their mass support base, nor explicitly condone the practice and risk losing the support of important internal and international constituencies thereby giving the apartheid state the upper hand in a discursive war on the moral and political legitimacy over using violence. Yet, I argue, this ambivalence was not merely a tactical one in that underlying the liberation discourse on the practice of necklacing was/is an inherent formulation of the binary of resistance and oppression/repression. The practice understood within this framework could only be rendered as state violence or resistance. In rendering it as the latter, though uncomfortably so, the ANC and UDF proposed that it be understood within a causal framework, as the result of oppression/repression. Ambivalence about the practice of necklacing thus, I argue, was produced in the interstice of the resistance - oppression/repression binary. Leading from this, I argue more broadly that the problematic of violence and attending ambivalence within the ANC has a history that predates the discourse around necklacing. I suggest that necklacing refuses to be forgotten precisely because of its ambivalence. Indeed, it may be that the inescapable ambivalence of necklacing is the condition for the possibility that it will always also be remembered.